Tổng hợp và ngưng tụ 2-metoxy-4-(3-metylfuroxan-4-yl)-5-nitrophenoxiaxetyl-hydrazin với một số andehit thơm - Lan, Hoàng Thị Tuyết; Dĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2012)
2-Methoxy-4-(3-methylfuroxan-4-yl)-5-nitrophenoxyacetylhydrazine synthesized from 2-methoxy-4-(3-methylfuroxan-4-yl)-5-nitrophenoxyacetic acid was condensed with aromatic or heterocyclic aldehyde to give nine hydrazide-hydrazones. The structure of reported compounds have been confirmed by IR, 1H-NMR  and 13C-NMR spectra. It is shown that the hydrazide-hydrazones exist as  syn  and anti conformers at CO-NH hydrazide single bond.